MEDIA POBSGI (POP UP BOOK SUMBER ENERGI) ILMU PENGETAHUAN ‘’ SUMBER ENERGI’’ DI KELAS III SDN GN. PICUNG 08 - Maulida, Wildatul; Lestari, Hana (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The background (needs analysis) of this research is motivated by the existence of problems which are known to exist students who lack understanding of science learning materials, especially in energy sources material in class III, as well as the lack of facilities in schools so that media is needed to support learning, one of which is pop up books for increase students' learning motivation towards material that is poorly understood in science learning on energy sources in class 3 subtheme 1 at SDN GN. Picung 08 in this study uses research and development with models but is limited only to development. So with that it is necessary to research POBSGI learning media (energy source pop up book). The validator results were carried out by 2 validators, namely material experts and media experts, this learning media obtained a score of 85.88% material expert and 87% media expert As for the two numbers obtaining values above the average, the results of the study are categorized as '' very worth it'' With the results of these presentations, this media is feasible to be tested as a development of learning media.